When motion improves working memory. Issue 3 (16th March 2019) - Plancher, Gaën; Mazeres, Florence; Vallet, Guillaume T.
ABSTRACT: In the present study, we used a complex span task to explore how memory traces resulting from Self-Performed Task (SPT) and Verbal Task (VT) are maintained in working memory. Participants memorised series of five sentences describing an action either through SPT or VT. Between pairs of sentences, participants performed a concurrent task that varied according to its nature and its cognitive load. The concurrent task was either a verbal task, a low cognitive load motor task or a high cognitive load motor task. A control condition served as a baseline. First, we observed that performance in SPT and VT did not decrease with verbal or motor suppression, but was lower with an increase of the cognitive load. This suggests that memory traces are maintained through attentional refreshing whatever the encoding (SPT or VT). Second, while the enactment effect was replicated in the control condition, it tended to vanish with a verbal concurrent task; moreover, it was reversed with motor concurrent tasks. Surprisingly, the latter effect resulted from an increase of VT memory performance when participants repeated the same gesture between sentences. Finally, our results provide additional evidence that the enactment effect does not rely on attention.